Unsung Heroines: Early Women Contributors to Adult Education - Susan Imel; Gretchen Bersch (Adult Education Research Conference, 2014)
The lives of 26 women, who contributed to adult education sometime during the period 1925 to 1950, were analyzed for common themes. Themes included the role of the Carnegie Foundation, leadership, advocacy, and discussion-based adult education.